2009
DOI: 10.7150/ijbs.5.244
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and coronary artery disease. The effect of gender and diabetes

Abstract: Background: The developmental origin theory of coronary heart disease proposes that undernutrition in utero permanently changes body functions and metabolism leading to an increased risk of coronary artery diseases (CAD) in adult life. Some studies support this theory but others suggest that birth weight (BW) is not a major risk factor for cardiovascular diseases. Gender differences concerning the association between BW and risk factors for CAD have been reported in some studies but not in others. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Since then, there have been many epidemiological studies in many populations worldwide that have confirmed these observations [ 3 , 11 , 15 , 30 , 31 , 32 , 33 , 34 , 35 ]. Of particular interest are the findings of the Nurses’ Health Study in which the health of 121,700 women in the USA was retrospectively followed up from 1976 and interestingly, the strong associations between low birth weight and coronary heart disease remained after adjustments were made for adult smoking, physical activity, dietary habits and socio-economic status [ 3 ].…”
Section: Low Birth Weight Is Linked To Long-term Cardiovascular DImentioning
confidence: 93%
“…Since then, there have been many epidemiological studies in many populations worldwide that have confirmed these observations [ 3 , 11 , 15 , 30 , 31 , 32 , 33 , 34 , 35 ]. Of particular interest are the findings of the Nurses’ Health Study in which the health of 121,700 women in the USA was retrospectively followed up from 1976 and interestingly, the strong associations between low birth weight and coronary heart disease remained after adjustments were made for adult smoking, physical activity, dietary habits and socio-economic status [ 3 ].…”
Section: Low Birth Weight Is Linked To Long-term Cardiovascular DImentioning
confidence: 93%
“…(Gilbert and Nijland 2008). Banci et al (2009) compared birth weight among subjects with coronary artery diseases and a control group. Their results showed a stronger correlation between low birth weight and coronary artery diseases in women.…”
Section: Discussionmentioning
confidence: 99%
“…Although some epidemiological studies have reported an inverse association between BW and risk of CHD, 18,23,26 others have reported no significant association or a positive association between BW and risk of CHD. 21,22 Moreover, in the reports of Danish birth cohort by Osler et al, 27 a U-shaped relationship was observed between BW and risk of CHD. Therefore, we carried out a meta-analysis to further identify the association between BW and subsequent risk of CHD.…”
Section: Introductionmentioning
confidence: 95%
“…8,17 To date, many studies have suggested that there is a significant relationship between birthweight (BW) and the risk for CHD. [18][19][20][21][22][23][24][25][26][27][28] Nevertheless, this relationship is inconsistent. Although some epidemiological studies have reported an inverse association between BW and risk of CHD, 18,23,26 others have reported no significant association or a positive association between BW and risk of CHD.…”
Section: Introductionmentioning
confidence: 99%